My jazz lecture note : the social meaning of the act of improvisation by Malaysian college students. - Chan, Cheong Jan (Universiti Putra Malaysia Press, 2012)
In this chapter, the contrasting outcomes on decoding the act of jazz improvisation from literature published in the last ten years will first be reviewed. These present thinking of jazz improvisation will then be reflected upon my own walk as a jazz piano instructor until now in Malaysia, by highlighting a particular case where a female student has experienced the dynamic of perceptive change which in turn caused the formal change in her act of improvisation. Issues that lie underneath the musical act of improvisation of Malaysian students are then discussed; they include the understanding of jazz (where it is a act of conformity or not), self-perceptions, self-esteem and gender.